The Relation of Leadership Style and Organization Culture with Quality of Care Service in Tiara Hospital Pematangsiantar - Pardede, Benny M. Y.; Hakim, Lukman; Sembiring, Evarina (Sari Mutiara Indonesia University Press, 2018)
The quality of hospital care service is influenced by various factors, such as leadership style and organization culture those are developed and implemented by all nurses in a hospital. This study aims to analyze the relationship between leadership style and organization culture with the quality of care services at Tiara Hospital in Pematangsiantar. The subjects of the study were 45 nurses at Tiara Hospital as samples. Data collection was conducted using a questionnaire and analyzed statistically using data analysis that used bivariate statistical tests, named Chi Square and continued with multivariate statistical tests. Organization culture carried out at Tiara Hospital in medical services is developed based on the values ​​and norms adopted by the hospital. The results of statistical analysis showed the variables of organization culture of innovation and risk taking, detailed attention, results orientation, human orientation, team organization, aggressiveness, stability related to the quality of hospital care services. Variable participatory leadership style is the most dominant factor related to the quality of service at Tiara Hospital (OR = 13,333) meaning that the possibility (opportunity) of nurses is able to provide good quality care services 13 times if the participatory leadership style is well done compared to the nurse which stated that participatory leadership style is not good at Tiara Hospital. It is suggested to the head of Tiara Hospital in Pematangsiantar, especially the head of the room needs to apply a leadership style that leads to participatif style. The leadership applied by the head of the room is always adjusted to the needs of the organization and pay attention to the situation and conditions that exist. Nurses at the Tiara Hospital in Pematangsiantar are expected to improve the understanding of the leadership style that has been done by the head of the room and try to implement the organization culture into a good work culture